Does fasting during Ramadan influence the therapeutic effect of warfarin?. (14th September 2020) - Sridharan, Kannan; Al Banna, Rashed; Qader, Ali Mohamed; Husain, Aysha
Abstract: What is known and objectives: The changes in the therapeutic effect of warfarin during Ramadan fasting are controversial. Hence, we carried out the present study to assess if there are any alterations in the anticoagulation response to warfarin and identify the associated risk factors. Methods: Patients receiving warfarin for at least 1 year were included in the present study. Their demographic details, warfarin doses, prothrombin time‐international normalized ratio (PT‐INR) values and concomitant diseases/drugs were retrieved. The dates of Ramadan periods for the calendar years were obtained, and these periods were considered as Ramadan periods. One month before the start dates of Ramadan was considered as pre‐Ramadan, and 1 month later than the last dates was considered as post‐Ramadan periods. Warfarin sensitivity index (WSI), PT‐INR category and time spent in therapeutic range (TTR) were assessed. National Institute of Clinical Health Excellence (NICE) criteria for anticoagulation status were adhered to where TTR (%) <65 was considered as poor anticoagulation. Results and discussion: One hundred and eighty‐three patients were recruited. No significant differences were observed in warfarin doses between the study participants between pre‐Ramadan, Ramadan and post‐Ramadan periods. Significantly more numbers of PT‐INR tests were carried out during Ramadan compared with pre‐ and post‐Ramadan periods. A higher WSI was akin to PT‐INR, and lower intra‐individual variability was observed in middle‐aged and older adults in the post‐Ramadan period. Significantly fewer patients had their PT‐INR in the therapeutic range and more in the subtherapeutic range during Ramadan periods. Greater proportion of patients had PT‐INR in the supratherapeutic range during post‐Ramadan periods, particularly the elderly. Although 38.3% had poor anticoagulation status overall, 92.4% met the NICE criteria for poor anticoagulation during the 3 months (pre‐Ramadan, Ramadan and post‐Ramadan periods). What is new and conclusion: Ramadan fasting influences the therapeutic effect of warfarin in terms of lowered TTR (%), reduced proportion of patients achieving therapeutic PT‐INR and increased risk of poor anticoagulation control. Greater caution is required during the post‐Ramadan period, particularly in the elderly category as they are more prone for over‐anticoagulation and consequently the risk of bleeding. Abstract : Patients receiving warfarin are more likely to have poor anticoagulation control during Ramadan period. A greater warfarin sensitivity and lower intra‐individual variability were observed in the post‐Ramadan period. During post‐Ramadan period, more patients are likely to present with supra‐therapeutic anticoagulation.